Granulocytic Sarcoma Presenting as Atypical Mastoiditis with Facial Paralysis: Description of a Case - Crovetto, M.; Márquez, J. A.; Ereño, C.; Elexpuru, J.; Crovetto, R.; Martinez, A. (Case Reports in Otolaryngology, 2011)
We describe a case of temporal granulocytic sarcoma in a 26-year-old patient after apparent molecular remission of an acute myeloid leukaemia. He complained of otodynia with hearing loss and facial paralysis on the right side. He was treated with chemotherapy and self-transplant haematopoietic stem cells. He was cured clinically, molecular remission of the haematological processes was achieved, and he remained asymptomatic for three years. Facial paralysis and hearing loss associated with temporal GS should be treated with chemotherapy. Aggressive surgery may complicate the clinical course of the disease and it should be avoided.